Medical student attitudes and perceptions of psychedelic-assisted therapies - Li, Irene; Fong, Rodney; Hagen, Molly; Tabaac, Burton (Frontiers in Psychiatry, 2023)
Introduction: Although certain psychedelic agents may soon gain federal approval for use in treating specific psychiatric conditions, the utilization of such therapies in clinical practice will depend largely on the attitudes of healthcare providers. Therefore, this study assesses the current attitudes, knowledge, exposure, and acceptance of psychedelics and psychedelic-assisted therapies amongst medical students. Methods: In fall semester of 2022, surveys were emailed to 580 medical students attending medical institutions in the state of Nevada in the United States. Utilizing knowledge and attitude items from previously published studies, the survey collected demographic data and assessed student attitudes with five-point Likert-scale variables. Data was analyzed using summary statistics and Kruskal-Wallis tests for differences in mean survey scores (i.e., attitudes towards psychedelics) based on demographic factors. Results: 132 medical students participated in the survey (22.7% response rate). Medical students demonstrated overall positive attitudes towards psychedelics, lack of knowledge regarding psychedelics, and uncertainty towards neurocognitive risks of psychedelics. Overall, 78.6% of students agreed that psychedelics have therapeutic potential, while 95.2% agreed that psychedelics deserves further research in assessing this potential. Additionally, there was no statistically significant effect of demographic variables, including age, sex, and level of training, on attitudes. Discussion: Although students are overall curious and optimistic about psychedelics, they demonstrate a lack of knowledge regarding recent research efforts. As the field of psychiatry prepares to implement psychedelics and psychedelic-assisted therapies, education and awareness of such agents should be initiated early on in medical clinical training.